UTERINE BLOOD FLOW DURING PERIPARTUM PERIOD IN BUFFALO AND ITS ASSOCIATION WITH SHEDDING OF PLACENTA - SINGH, N; GANDOTRA, VK; GHUMAN, SPS; DHINDSA, SS; BRAR, PS (The Indian Journal of Animal Reproduction, 2016)
Twenty-three normal calving buffalo were subjected to trans-rectal doppler sonography to assess the blood flow in ipsilateral (IpsiUA, side of pregnant horn) and contralateral (ContUA) uterine artery in relation to shedding of placenta within 6 h post-calving (n=18) or later (n=5). Doppler parameters viz. time average peak velocity TAP), blood flow volume (BFV), and resistive (RI) and pulsatility index (PI) were measured immediately before the start of calving process, and at 30 min and 6 h post-calving. The values of TAP and BFV in the uterine artery recorded at the start of calving process invariably exhibited a decreasing trend by 30 min post-calving which continued till 6 h post-calving (p<0.05). The values of RI and PI in uterine artery ipsilateral to side of pregnancy increased consistently till 6 h post-calving as compared to pre-calving values (p<0.05). At 6 h post-calving, both in IpsiUA as well as ContUA, the values of TAP and BFV were higher (p<0.05), and RI and PI were lower (p<0.05) in buffalo that failed to shed placenta within 6 h post-calving in comparison to their counterparts taking >6 h after calving for shedding placenta. In conclusion, the reference values for doppler indices for uterine artery during peripartal period were generated and it was observed that the decrease observed in blood flow in uterine artery was slow in buffalo with delayed shedding of placenta.